1980
DOI: 10.1099/0022-1317-47-1-79
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Pathogenesis-related Proteins from Plants of Two Cultivars of Tobacco Infected with TMV

Abstract: SUMMARYA procedure is described for purifying the bl, b2 and b3 proteins from leaves of Nieotiana tabacum cv. Xanthi-nc, a cultivar reacting hypersensitively to tobacco mosaic virus (TMV). All three proteins consist of a single polypeptide, have similar mol. wt. of about ]4 2oo but differ in charge. In contrast, the b4 protein differs from bl to b3 in both charge and size. The same procedure purifies the proteins IV, III and II from TMV-infected leaves of N. tabacum cv. Samsun NN. The Samsun NN proteins IV to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
97
0
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 230 publications
(107 citation statements)
references
References 3 publications
4
97
0
2
Order By: Relevance
“…PR-1 has antifungal properties but the microbial targets are unkonwn. 27 The proposed antimicrobial target of PR-2 is the fungal cell wall component β-1,3 glucan. 28 PR-3 and PR-4 have chitinase activity.…”
Section: Methodsmentioning
confidence: 99%
“…PR-1 has antifungal properties but the microbial targets are unkonwn. 27 The proposed antimicrobial target of PR-2 is the fungal cell wall component β-1,3 glucan. 28 PR-3 and PR-4 have chitinase activity.…”
Section: Methodsmentioning
confidence: 99%
“…wt. of PR 1 a has been estimated at approximately 14 500 by analytical; ultracentrifugation and amino acid analysis (Antoniw et al, 1980). However, PR 1 proteins la, lb and lc behave anomalously during electrophoresis in denaturing conditions and comigrate with an apparent mol.…”
mentioning
confidence: 99%
“…Pathogenesis-related (PR) proteins (Antoniw et al, 1980), also known as b-proteins, were first identified in leaves of tobacco plants infected with tobacco mosaic virus (TMV) (Gianinazzi et al, 1970;Van Loon & Van Kammen, 1970). It has since been shown that PR proteins are induced by other viruses, by bacteria and by fungi (Kassanis et al, 1974;Ahl et al, 1981;Gianinazzi et al, 1980).…”
mentioning
confidence: 99%
See 2 more Smart Citations